Recovery experiences and burnout among female compulsory school teachers in Sweden - Niclas Almén; Sofie Svensson; Mikaela Ekroth; Billy Jansson (Cogent Psychology)
Teachers are particularly affected by stress and burnout. Recovery experiences are crucial to counteract the harmful continuation of everyday life stress reactions. There is a lack of knowledge regarding recovery experiences and its importance for burnout among compulsory school teachers. The aim of the present study was to investigate (1) the levels of burnout and different recovery experiences during leisure time among female compulsory school teachers in Sweden, and (2) to which extent different recovery experiences explain burnout. In a non-random sample of female compulsory school teachers (n = 570) and a random sample from a general female working population (n = 457/393), the participants self-rated their levels of burnout and their recovery experiences during leisure time via the brief version of the Shirom-Melamed Burnout Measure and the Recovery Experience Questionnaire, respectively. Independent t-tests showed that, compared to the general female working population, the female compulsory school teachers scored (1) significantly higher on burnout (with a high magnitude of effect, d = 0.87), and (2) significantly lower on recovery experiences (d = 0.38–1.23). In total, recovery experiences explained 37% of the variance in burnout. Among the four recovery experiences being investigated, Psychological detachment explained the highest variance in burnout (27%), with Mastery and Control also being significant predictors in the model. Surprisingly, the variance of Relaxation in explaining burnout was close to zero. The study suggests enhancing the circumstances that foster psychological detachment among female compulsory school teachers in Sweden and further investigation of recovery experiences among teachers.